EMPOWERMENT OF UMKM ACTIVITIES THROUGH CSR PROGRAM OF PT. TIRTA INVESTAMA PLANT SUBANG - Lia Yuliana; Riani Laila Nurwulan; Bustan Arif (JEES: Journal of Economic Empowerment Strategy, 2022)
This study aims to describe the impact of implementation of a program related to corporate social responsibility (CSR) in the community economic empowerment program ( Ecodev ) PT. Tirta Investama (Aqua) by the West Java Human Initiative as a program implementing partner in Subang Regency. The concept used in this study uses the Triple Bottom Line (3P) concept by John Elkington (1998), that corporate social responsibility (CSR) pays attention to improving the quality of the company (profit); provide benefits to the surrounding community (people); maintain the environmental sustainability of the operating area (planet). This research focuses on the implementation of corporate social responsibility in an effort to community empowerment which is stated by Sumodiningrat (1999) that, “community empowerment is an effort to make community independent through the realization of their own potential abilities. In line with this, Bernadib stated that "Independence includes the behavior of being able to take the initiative, being able to solve problems, having selfconfidence , being able to do things without depending on others". This study uses a qualitative approach using secondary data analysis. Data collection techniques used are document studies and literature review. Analysis of the validity of the data using the stages of data triangulation, thick and rich description, and prolonged time. Data analysis techniques using coding and categorization. The results of the study revealed that the community economic empowerment program ( Ecodev ) of PT. Tirta Investama Plant Subang has an impact on the independence of business actors marked by the emergence of innovations in developing businesses which are facilitated by the West Java Human Initiative as a facilitator.